2004
DOI: 10.1002/cphc.200400281
|View full text |Cite
|
Sign up to set email alerts
|

Torsional Barriers in Aromatic Molecular Clusters as Probe of the Electronic Properties of the Chromophore

Abstract: We present a computer program that is capable of fitting n-fold torsional barriers Vn (n = 2-6) and torsional constants F simultaneously to high- and low-resolution spectroscopic data of different isotopomeric internal rotors. The program has been utilized to fit independently barriers and torsional constants for both electronic states of several aromatic clusters. The constant F of the ammonia moiety in the phenol-ammonia cluster is shown to decrease upon electronic excitation, thus imaging the formation of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…The derived barrier heights from the high resolution spectrum of phenol-H 2 O, 4 using the 1D analysis, are V 2 = 177 and V 2 = 127 cm −1 . Jacoby and Schmitt 35 have suggested that the decrease in V 2 upon excitation observed in phenol-H 2 O arises from the loss of the second C − H · · · OH 2 HB. This hypothesis appears consistent with the data presented here on cis-2HNW (V 2 = 180 cm −1 ), as well as a subtle photoinduced change in α (α = 18.5, α = 30.6 • ) that may result from a less favorable secondary interaction between H 2 O and the naphthalene ring.…”
Section: A S 0 and S 1 Structures Of Cis-2hnwmentioning
confidence: 98%
See 2 more Smart Citations
“…The derived barrier heights from the high resolution spectrum of phenol-H 2 O, 4 using the 1D analysis, are V 2 = 177 and V 2 = 127 cm −1 . Jacoby and Schmitt 35 have suggested that the decrease in V 2 upon excitation observed in phenol-H 2 O arises from the loss of the second C − H · · · OH 2 HB. This hypothesis appears consistent with the data presented here on cis-2HNW (V 2 = 180 cm −1 ), as well as a subtle photoinduced change in α (α = 18.5, α = 30.6 • ) that may result from a less favorable secondary interaction between H 2 O and the naphthalene ring.…”
Section: A S 0 and S 1 Structures Of Cis-2hnwmentioning
confidence: 98%
“…The two HB lengths in Fig. 1 are predicted by theory to be 1.89 and 2.74 Å, respectively Jacoby and Schmitt 35 have developed a program (called HTORFIT) in which "best fit" values of F and V n for 1:1 complexes are determined using all available vibrationally and rotationally resolved experimental data. From a global fit of all experimental data, they find that V 2 = 175.4 (13) cm −1 and V 2 = 109.1 (2) cm −1 for phenol-H 2 O.…”
Section: A S 0 and S 1 Structures Of Cis-2hnwmentioning
confidence: 99%
See 1 more Smart Citation
“…In two recent publications 3,28 we showed how a combined fit to high-resolution rovibronic data and lowresolution torsional transitions can be used to improve the determination of the barriers and torsional constants in both electronic states. A, B, C, V 3 , V 6 , F, and were fitted for each electronic state to the rotationally resolved origin and to the torsional transitions from Ref.…”
Section: A 4-methylphenolmentioning
confidence: 99%
“…The theory of coupling of the two‐fold internal rotation of the water moiety to the overall rotation of the cluster has been elaborated in detail in refs. 1 and 29 and will not be repeated here. The upper trace of Figure 1 shows the experimental spectrum, the following trace the complete simulation using the parameters from Table 1.…”
Section: Resultsmentioning
confidence: 99%